Extracellular vesicles as mediators of neuron-glia communication - Frühbeis, Carsten; Fröhlich, Dominik; Kuo, Wen Ping; Krämer-Albers, Eva-Maria (Frontiers in Cellular Neuroscience, 2013)
In the nervous system, glia cells maintain homeostasis, synthesize myelin, provide metabolic support, and participate in immune defense. The communication between glia and neurons is essential to synchronize these diverse functions with brain activity. Evidence is accumulating that secreted extracellular vesicles (EVs), such as exosomes and shedding microvesicles, are key players in intercellular signaling. Among others, the cells of the nervous system secrete EVs, which carry protein and RNA cargo from one cell to another. After delivery, the cargo has the ability to modify the target cell phenotype. Here, we review the recent advances in understanding the role of EV secretion by astrocytes, microglia, and oligodendrocytes in the central nervous system. Current work has demonstrated that oligodendrocytes transfer exosomes to neurons as a result of neurotransmitter signaling suggesting that these vesicles may mediate glial support of neurons.